Opportunities for Addressing the Nursing Crisis in Colombia - Claudia Marcela Velásquez Jiménez; Dedsy Yajaira Berbesi Fernández (Aquichan, 2026)
Professional nursing in Colombia faces structural challenges that, despite their severity, remain marginalized in the public agenda and in the formulation and implementation of health sector policies. Employment precarization, contractual instability, delayed salary payments, limited recognition of postgraduate education, and excessive workloads undermine professional practice and adversely affect the quality of care. These challenges are compounded by a critical shortage of nurses: Colombia has only 1.6 nurses per 1,000 inhabitants, a ratio substantially lower than the average reported by the Organisation for Economic Co-operation and Development (OECD), and also has the lowest nurse-to-physician ratio in Ibero-America, with 1.5 nurses for every five physicians. This shortage creates gaps in healthcare coverage and facilitates professional encroachment by individuals who lack the required qualifications, thereby compromising patient safety, increasing the risk of preventable adverse events, and weakening the healthcare system's capacity to provide safe, high-quality care.